KARDIOCHIRURGIA DOROSŁYCHHypoglycaemic treatment and metabolic control in patients with diabetes referred for planned heart surgery - Ruprecht, Zoﬁa; Kamińska, Anna; Lau, Grzegorz; Anisimowicz, Lech; Junik, Roman (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: Subjects with diabetes comprise 13-37% of patients undergoing coronary artery bypass graft surgery (CABG). In clinical practice the problems of metabolic control and preoperative hypoglycaemic management are often underestimated. Aim: The aim was to determine the hypoglycaemic treatment and metabolic status of patients referred for heart surgery (94.4% CABG). Material and Methods: 72 patients with diabetes (92% type 2, 8% type 1), mean age 63 ± 8 years, diabetes duration 10 ± 8.6 years, were examined by a diabetologist in the Outpatient Clinic, in order to evaluate their metabolic status before planned heart surgery. Results: Mean systolic and diastolic blood pressure was 135 ± 17.5 and 76 ± 10.5 mm Hg, respectively, HbA1c 6.7 ± 1.9%, total cholesterol 180 ± 53.5 mg/dl, LDL 98.1 ± 37.0 mg/dl, HDL 52 ± 13.2 mg/dl, triglycerides 173 ± 142.6 mg/dl. Recommended systolic (< 130 mm Hg) and diastolic (< 80 mm Hg) blood pressure value was achieved in 47.2% and 79.2% of patients, respectively. HbA1c ≤ 7.0% was achieved in 66.7% of patients, total cholesterol < 175 mg/dl in 56.9%, LDL < 100 mg/dl (and in patients with ischaemic heart disease 40 in men and > 50 in women) in 70.4%, triglycerides < 150 mg/dl in 56.2% of patients. All of the therapeutic goals were achieved in 5.9% of patients. The hypoglycaemic treatment was modified in 72% of patients. Conclusions: Mean HbA1c, blood pressure and lipid parameters did not considerably exceed recommended values. A substantial proportion of patients however, did not achieve the therapeutic goals, were not properly prepared before surgery and required intensification of treatment.